2022
DOI: 10.1186/s10194-022-01480-2
|View full text |Cite
|
Sign up to set email alerts
|

Does MIDAS reduction at 3 months predict the outcome of erenumab treatment? A real-world, open-label trial

Abstract: Background In Italy, monoclonal antibodies targeting the CGRP pathway are subsidized for the preventive treatment of high frequency and chronic migraine (CM) in patients with a MIgraine Disability ASsessment (MIDAS) score ≥ 11. Eligibility to treatment continuation requires a ≥ 50% MIDAS score reduction at three months (T3). In this study, we evaluate whether a ≥ 50% MIDAS score reduction at T3 is a reliable predictor of response to one-year erenumab treatment. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…This finding that at least one ≥50% response rate in any of months 1–3 could be a better predictor of favorable outcome at 6 months is very important to motivate patients to continue CGRP monoclonal antibodies in a clinical setting where the MMD value is susceptible to climate change, stress, and other factors depending on each patient. In line with our results, a long-term open-label study showed that a ≥ 50% reduction in MMDs at month 3 after initiation of erenumab treatment could predict 1-year outcome, but combinations of ≥50% response rates at 1–3 months were not evaluated ( 24 ).…”
Section: Discussionsupporting
confidence: 83%
“…This finding that at least one ≥50% response rate in any of months 1–3 could be a better predictor of favorable outcome at 6 months is very important to motivate patients to continue CGRP monoclonal antibodies in a clinical setting where the MMD value is susceptible to climate change, stress, and other factors depending on each patient. In line with our results, a long-term open-label study showed that a ≥ 50% reduction in MMDs at month 3 after initiation of erenumab treatment could predict 1-year outcome, but combinations of ≥50% response rates at 1–3 months were not evaluated ( 24 ).…”
Section: Discussionsupporting
confidence: 83%
“…Although with some discrepancies, positive post-hoc predictors of treatment success and treatment-induced changes associated with good outcome were also identified in real-world studies, most of them with erenumab (Table 1 ): headache unilaterality [ 52 , 53 ], cranial autonomic attack symptoms [ 54 ], higher baseline migraine frequency [ 51 , 55 ], less severe disability at baseline [ 34 , 55 ], absence of other primary headaches [ 28 , 56 ], good response to triptans [ 23 , 53 , 55 ], typical migraine features and vomiting [ 23 ], young age [ 36 ], and a 50% response after 3 months of treatment [ 57 ]. In experimental studies, responders to erenumab had higher susceptibility to attack induction by the intravenous administration of CGRP [ 58 ], higher pre-treatment salivary CGRP levels [ 59 ], increased thresholds of the biceps femoris withdrawal reflex at 3 months [ 60 ], lower serum CGRP levels at 4 weeks [ 61 ], and less iron accumulation in the periaqueductal gray and anterior cingulate cortex at 8 weeks post-injection [ 62 ].…”
Section: Are There Any Outcome Predictors?mentioning
confidence: 99%
“…In clinical practice very few patients may benefit from a switch to a 3rd anti-CGRP/rec mAb. If switching is considered after 12 weeks of treatment, a timepoint at which most patients will have responded or not [ 57 ], one has to take into account the recent results from an Italian registry showing that 146 out of 265 non-responders (55.1%) to an anti-CGRP/rec mAb at 12 weeks have nevertheless a 50% response after 24 weeks [ 71 ].…”
Section: Is Switching Between Anti-cgrp/rec Mabs Useful?mentioning
confidence: 99%
“…Similarly, a long-term effectiveness study of three CGRP pathway mAbs found that ≥ 50% reduction in MIDAS score was achieved by 89.5% of patients compared with 36.4%–56.8% for MMD at Month 6, with authors concluding that the MIDAS score was the most advantageous efficacy scale in this setting [ 42 ]. In this context, however, a RWE study of 77 patients with CM treated with erenumab showed that a ≥ 50% reduction in MIDAS score at 3 months excluded more than one third of responders at Month 12, thus suggesting that the combined use of a reduction in MIDAS score and MMD could better reflect the proportion of patients who can benefit from treatment with CGRP pathway mAbs [ 43 ]. This discrepancy may be explained by the fact that MIDAS score indirectly reflects the intensity of migraine, while MMD reflect purely the number of days with migraine, regardless of their intensity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%